Salinity and subsequent freshwater influences on the growth, biomass, and polyisoprenoids distribution of Rhizophora apiculata seedlings - MOHAMMAD BASYUNI; MASRIDA WASILAH; POPPY ANJELISA ZAITUN HASIBUAN; NURDIN SULISTIYONO; SUMARDI SUMARDI; YUNTHA BIMANTARA; RAHMAH HAYATI; HIROSHI SAGAMI; HIROSUKE OKU (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Basyuni M, Wasilah M, Hasibuan PAZ, Sulistiyono N, Sumardi, Bimantara Y, Hayati R, Sagami H, Oku H. 2019. Salinity and subsequent freshwater influences on the growth, biomass, and polyisoprenoids distribution of Rhizophora apiculata seedlings. Biodiversitas 20: 388-395. This study described the growth, biomass, and polyisoprenoids (polyprenol and dolichol) distribution of Rhizophora apiculata seedlings under saline and subsequent fresh water treatment. Propagules of R. apiculata were collected from Pulau Sembilan, Langkat, North Sumatra and were grown in 0.0%, 0.5%, 1.5%, 2.0%, and 3.0% salt concentrations for three months. After three months planted in a glass house, R. apiculata seedlings were divided into two groups and grown for another three months. The first group was continuously grown under the saline condition and the second was moved to fresh water to recover from the saline condition. The leaves, stems, and roots of R. apiculata seedlings were harvested after six months of cultivation. Polyisoprenoids alcohol was isolated from the leaves and roots of R. apiculata seedlings and analyzed using two-dimensional thin layer chromatography. Growth parameters measured were height and diameter of R. apiculata seedlings. The height of R. apiculata seedlings was significantly affected by salinity levels of 2.0%, 3.0% and 3.0% ? 0.0%. The arrow (?) denoted fresh water recovery treatment. The best height and diameter of R. apiculata seedlings were observed in 0.5% salt concentration. Salinity treatment and re-adaptation into freshwater significantly influenced the leaves area (2.0%, 3.0% and 3.0% ? 0.0%), fresh weight of stem (3.0% and 3% ? 0.0%) and stem dry weight (3% ? 0.0%). Distribution of polyprenols and dolichols in the leaves and roots of R. apiculata seedlings were categorized as type I, where dolichol was dominant over polyprenol. Under salinity and subsequent fresh water recovery treatments (0.0%, 1.5%, 1.5% ? 0.0%, 3.0%, and 3.0% ? 0.0%), the carbon chain length of dolichol in the leaves and in the roots was, respectively, C85-C100, C85-C100, C85-C105, C85-C100, C85-C95 and C85-C105, C85-C105, C85-C105, C85-C110, C85-C100. These data suggested the significant role of polyisoprenoids in mangrove plants to withstand salt stress and or water stress.